JERUSALEM: A TALE OF A CITY - Mandour, M. Alaa (Journal of Islamic Architecture, 2011)
World class cities are few and far between, sometimes referred to as â€˜global citiesâ€™ or simply â€˜world citiesâ€™. There are no more than a dozen metropolitan areas in the world that can claim Â this kind of global status. London, Â New Â York, Â Paris, Â and Â Tokyo Â sit Â at Â the Â top Â of Â this Â world Â city Â hierarchy. They Â have Â enormous concentrations of economic, political, and cultural clout â€“ measured by such things as the number of corporate headquarters, the size of their stock exchanges, the presence of national and international political bodies, and their role in music, fashion, and other cultural activities. What would it take to make a city claimed by two nations and central to three religions â€œmerelyâ€ a city, a place of difference and diversity in which contending ideas and citizenries can co-exist in benign yet creative ways? The intractable conflicts in the Middle East and the cycle of violence among Israelis and Palestinians are deeply embedded in historical struggles over national sovereignty and the right to territory. For this reason, questions about whose state will prevail in what physical location have defined the terms of conflict and negotiation. This also has meant that most proposed solutions to Â â€œthe Â Middle Â East Â problemâ€ Â have Â revolved Â around Â competing Â claims Â of Â nation-states, Â their Â rights Â to existence, and their physical and juridically-sanctioned relationships to each other. While true generally, this framing of the problem has been especially dominant in the case of Jerusalem, a city that is geographically and historically an overlay of spaces and artifacts that carry deep meaning for competing peoples and nations. The current struggles of Palestinians and Israelis to each claim this hallowed ground as their capital city has added yet another layer of complexity, conflict, and political division, all of which is reflected in the competing/dual nomenclature Al-Quds/Jerusalem used to refer to the Â city â€“as well as the violence and contestation that continues to accelerate unabated. Â  Keywords: two nations, three religions, Jerusalem